2018
DOI: 10.1002/mabi.201800096
|View full text |Cite
|
Sign up to set email alerts
|

Strontium‐Substituted Hydroxyapatite‐Gelatin Biomimetic Scaffolds Modulate Bone Cell Response

Abstract: Strontium has a beneficial role on bone remodeling and is proposed for the treatment of pathologies associated to excessive bone resorption, such as osteoporosis. Herein, the possibility to utilize a biomimetic scaffold as strontium delivery system is explored. Porous 3D gelatin scaffolds containing about 30% of strontium substituted hydroxyapatite (SrHA) or pure hydroxyapatite (HA) are prepared by freeze-drying. The scaffolds display a very high open porosity, with an interconnectivity of 100%. Reinforcement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 39 publications
4
30
0
Order By: Relevance
“…Substitution of Sr 2+ ions at Ca 2+ sites in HA lattice is well reported (Frasnelli et al, 2017;Lowry et al, 2018;Šupovà, 2015;Terra et al, 2009). In literature there are several studies demonstrating that the incorporation of Sr into biomaterials efficiently trades cell activity (Panzavolta et al, 2018) and induces bone regeneration. It was demonstrated that Sr stimulates bone formation by playing a stimulatory role in osteoblast cells and an inhibitory role in osteoclast cells (Capuccini et al, 2008;Capuccini et al, 2009).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Substitution of Sr 2+ ions at Ca 2+ sites in HA lattice is well reported (Frasnelli et al, 2017;Lowry et al, 2018;Šupovà, 2015;Terra et al, 2009). In literature there are several studies demonstrating that the incorporation of Sr into biomaterials efficiently trades cell activity (Panzavolta et al, 2018) and induces bone regeneration. It was demonstrated that Sr stimulates bone formation by playing a stimulatory role in osteoblast cells and an inhibitory role in osteoclast cells (Capuccini et al, 2008;Capuccini et al, 2009).…”
Section: Introductionmentioning
confidence: 90%
“…are several studies demonstrating that the incorporation of Sr into biomaterials efficiently trades cell activity (Panzavolta et al, 2018) and induces bone regeneration.…”
mentioning
confidence: 99%
“…The composite scaffolds were developed by using a PCL polymeric matrix mainly for its good printability, biodegradability and for being an FDA approved biomaterial [ 49 ]. In relation to the ceramic phase, previous studies on Sr-containing biomaterials in various forms indicated that even small amounts of Sr (0.1 wt%) can enhance the osteoconductive properties of calcium phosphate, have a positive effect on bone mineralization, elevate the mechanical property of bone tissue and have crucial effects by inducing collagen type I synthesis [ 50 , 51 , 52 , 53 ]. Additionally, it has been reported that Sr can act via the calcium-sensing receptor and promote the transductions of the mitogen-activated protein kinase signaling.…”
Section: Resultsmentioning
confidence: 99%
“…This approach leads to a larger, effective functionalized area and 3D distribution of trace elements throughout the bulk material. Even small amounts of these ionic species substitutes in the structure of ceramics exert a significant effect on thermal stability, solubility, osteoclastic and osteoblastic responses, degradation and bone regeneration [53,54,[80][81][82][83][84].…”
Section: Discussionmentioning
confidence: 99%